Some Dynamic Inequalities of Hilbert's Type. (30th March 2020) - Ahmed, A. M.; AlNemer, Ghada; Zakarya, M.; Rezk, H. M.
Abstract : This paper is concerned with deriving some new dynamic Hilbert-type inequalities on time scales. The basic idea in proving the results is using some algebraic inequalities, Hölder's inequality and Jensen's inequality, on time scales. As a special case of our results, we will obtain some integrals and their corresponding discrete inequalities of Hilbert's type.